Мифологический подтекст «мессианской» деятельности героя в трилогии «На ростанях» Я. Коласа - Михайловна Иоскевич, Марина (SlavVaria, 2024)
The Mythological Implication of the “Messianic” Activity of the Hero in the Trilogy “At the Crossroads” by Ya. Kolas. The article reveals the mythological sequence of the main character’s functions in the trilogy “At the Crossroads” by Ya. Kolas, which is recognized as one of the most significant Belarusian literary works on revolutionary theme. The full realization of the presented functional sequence forms the mythological subtext of the “Messianic” activity of the hero, reinforced by biblical allusions and reminiscences at the explicit level of the literary text, which contributes to the introduction of the social myth of the need for revolutionary transformations into the reader’s consciousness.